1993
DOI: 10.1002/jlb.53.4.390
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a human monocyte antigen, B148.4, regulated during cell differentiation and activation

Abstract: We analyzed the phenotypic changes associated with monocyte activation and differentiation using a newly developed monoclonal antibody (B148.4). Among peripheral blood leukocytes, the antigen recognized by this antibody is expressed on monocytes and granulocytes at high and low density, respectively. Antigen expression is lost during in vitro differentiation of monocytes and is absent on tissue macrophages, indicating that expression of this antigen is related to monocyte differentiation. Only 1 alpha,25-dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Human peripheral blood mononuclear cells were obtained from heparinized blood by Ficoll-Hypaque density gradient. Monocytes were then isolated by adherence to culture flasks as described [28]. For cell aggregation, monocytes were cultured in the presence or absence of C10 or C40 for 72 h. Cell colonies were monitored under an inverted phase contrast microscope coupled through a video camera to a computer.…”
Section: Methodsmentioning
confidence: 99%
“…Human peripheral blood mononuclear cells were obtained from heparinized blood by Ficoll-Hypaque density gradient. Monocytes were then isolated by adherence to culture flasks as described [28]. For cell aggregation, monocytes were cultured in the presence or absence of C10 or C40 for 72 h. Cell colonies were monitored under an inverted phase contrast microscope coupled through a video camera to a computer.…”
Section: Methodsmentioning
confidence: 99%
“…The MS-1 antigen is also found on in vitro differentiated monocytes/macrophages and on dendritic perivascular macrophages in situ (Goerdt et al 1994). The opposite regulation is found for the human antigen B18.4, which is highly expressed on monocytes but is lost during the differentiation into macrophages (Anegon et al 1993). All these antigens are expressed after in vitro differentiation of monocytes with serum and can therefore serve as maturation markers.…”
Section: Characterization Of Differentiation By Phenotypementioning
confidence: 98%
“…1992Krissansen et al 1990, Andreesen et al 1990aEzekowitz and Stahl 1988Zwadloetal. 1985Andreesen et al 1986, 1988aAndreesen et al 1986, 1988aAndreesen et al 1986, 1988aAnegon et al 1993Andreesen et al 1990aGoerdtetal. 1993.…”
Section: Characterization Of Differentiation By Phenotypementioning
confidence: 99%
“…Comparison between human blood monocytes and derived macrophages obtained after differentiation has demonstrated a modulation of phenotype [1][2][3][4][5][6]. Some works [7] have shown that in vitro maturation of blood monocytes into macrophages could be used as a model for studying the in vivo phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Some works [7] have shown that in vitro maturation of blood monocytes into macrophages could be used as a model for studying the in vivo phenomenon. Monocyte-derived macrophages generally express surface markers not found on their monocyte precursors [2,4,6,7]. The increase in the appearance of macrophage specific markers/activities is associated with a decrease in certain monocyte characteristics.…”
Section: Introductionmentioning
confidence: 99%